Preprocedural ultrasound vascular assessment is essential to decision-making. Issue 5 (September 2021) - Brescia, Fabrizio; Fabiani, Fabio; Borsatti, Eugenio; Parisella, Laura; Roveredo, Laura; Pittiruti, Mauro
Reliable venous access should be part of the clinical-therapeutic path of all cancer patients. A correct preliminary ultrasound evaluation of the patient's veins and the choice of the suitable vein are the fundamental requirements to guarantee a stable and long-lasting venous access.